Genetic diversity of edible Lepidoptera in Southern Africa and implications for sustainable use of wild populations - Nethavhani, Zwannda (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhDAgric)--Stellenbosch University, 2024.